Speaking presentation for powerpoint (SPFP) : To create self-speaking presentation with human-like voices. - Muhammad @ S A Khushren, Sulaiman (2021)
Microsoft PowerPoint help users deliver presentation using slides that composed of texts, graphics, sound and animation. Although the PowerPoint is packed with many features, but there are more features that can be added to improve productivity and creativity in creating presentation. I n that aspects, PowerPoint allow custom programs to be attached to PowerPoint to add that features, and these programs are called Add-ins for PowerPoint. Speaking Presentation for PowerPoint (SPFP) is an Add-ins program for PowerPoint. I t uses text-to-speech (TTS) technology in Windows to convert texts placed in Notes section of PowerPoint slides to human-like speaking voices. I n the early Windows operating system, the TTS technology produced a very poor generated human speaking sound. But currently, with Window 10, the sound generated is very life like human voices. The finished presentation when published is saved in html file format that can be viewed using I nternet browser.